A young lady with primary amenorrhea and virilization - Khan, Muhammad Abdul Halim; Morshed, Md Shahed; Sultana, Nusrat; Jahan, Sharmin; Aktar, Yasmin; Fariduddin, Md (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
An 18-year-old female presented with primary amenorrhea, absent development of breasts, and features of virilization. Investigations revealed high total testosterone and dehydroepiandrosterone-sulfate with normal cortisol and 17-hydroxyprogesterone. Her karyotype was 46XX. CT scan of the abdomen revealed a (4×3) cm sized left adrenal mass. Open adrenalectomy followed by histopathology of the resected adrenal showed a benign adenoma. The patient’s clinical and biochemical features improved within six months of surgery. Virilization usually indicates a malignant adrenal tumor, but surprisingly the cause may be a benign one. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2024; 3 (1): 31-33